A Novel Walkway System for Measuring the Spatial Gait Parameters of Rats with Spinal Cord Injury - Ya'akob Yusof; Mohd Nor Azmi Ab. Patar; Azim Patar; Jamaluddin Mahmud (International Journal of Integrated Engineering, 2025)
Changes in locomotion, especially related to spinal issues, can signal health conditions. Analysing spatial gait parameters is crucial for understanding these changes. Rats are frequently used in spine-related gait studies to enhance disease understanding, often with the assistance of complex gait analysis systems. Nevertheless, existing commercial systems for rat gait analysis are costly and lack customization options. This paper presents a new walkway system for measuring rat spatial gait parameters in spinal cord injury (SCI) cases. Thirteen adult female Wistar rats were randomly divided into two groups – uninjured (7) and injured (6). For the injured group, contusion SCI was inflicted on the T9/T10 thoracic area of the spinal cord using the NYU Impactor device. The system analyzed stride length (SL) and stance width (SW) and compared its output with manually obtained values. Reliability was assessed using Pearson correlation and Bland-Altman analysis, showing a high correlation (r > 0.94) and insignificant bias in measurements. Moreover, disagreement between the systems was less than 5% of the mean value in over 95% of measured outputs, showcasing the system’s reliability in measuring gait parameters in normal and SCI-injured rats. Furthermore, the system’s output indicates injury in the injured rats with shorter SL and larger SW compared to uninjured ones, demonstrating its capability. This system provides a low-cost setup that can be effectively used to enhance knowledge in studies related to SCI using rats as the model.